Capital, Alienation, and Challenge: How U.S. Mexican Immigrant Students Build Pathways to College and Career Identities. Issue 160 (6th April 2018) - Cooper, Catherine R.; Domínguez, Elizabeth; Cooper,, Robert G.; Higgins, Ashleigh; Lipka, Alex
Abstract: This article considers how the global "academic pipeline problem" constrains immigrant, low‐income, and ethnic minority students' pathways to higher education, and how some students build pathways to college and career identities. After aligning theories of social capital, alienation/belonging, and challenge and their integration in Bridging Multiple Worlds Theory, we summarize six longitudinal studies based on this theory from a 23‐year university–community partnership serving low‐income, primarily U.S. Mexican immigrant youth. Spanning from childhood to early adulthood, the studies revealed two overarching findings: First, students built pathways to college and career identities while experiencing capital, alienation/belonging, and challenges across their evolving cultural worlds. Second, by "giving back" to families, peers, schools, and communities, students became cultural brokers and later, institutional agents, transforming institutional cultures. Findings highlight the value of integrating interdisciplinary theories, research evidence, and educational systems serving diverse communities to open individual pathways and academic pipelines in multicultural societies.